Pengaruh Teori Seni Barat Dalam Desain Iklan - Budi Yuwono (AKSA: Jurnal Desain Komunikasi Visual, 2018)
Aesthetic has become a clear barometer to measure the beauty value of an artwork. It has been going from the classical era with a realistic style until the modern era which more directed to the applied art. Despite the advancement of the nowadays digital age, an artwork will taste bland when it ignoring these universal basic principles. Those principles are increasingly needed when an artwork turned into a message medium from communicator to communicant. Advertising design is an applied art, where on one hand it should consider the value of beauty of the ad to attract and seize people's attention. But on the other hand, advertising is a medium of visual communication. If the message is submitted by the advertiser and the media is received differently by the target goal, then the communication will failed. Thus the role of art theory as a universal principle need to be applied in ad designing. The application of the art theory must be tailored to the conveyed message and adapted to the present approach.